2016
DOI: 10.3389/fphar.2016.00494
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban-Induced Hemorrhage Associated with ABCB1 Genetic Defect

Abstract: We report a patient who presented a non-ST segment elevation myocardial infarction in the context of severe normocytic hypochromic anemia related to gastrointestinal bleeding, 3 months after switching anticoagulant from the vitamin K antagonist acenocoumarol to the direct oral anticoagulant rivaroxaban. High levels of both anti-Xa activity and rivaroxaban plasma concentrations were measured despite rivaroxaban withdrawal, suggesting reduced elimination/drug clearance. Estimated half-life was 2–3 times longer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 20 publications
(36 reference statements)
3
67
0
5
Order By: Relevance
“…20 Likewise, ABCB1 2677G > T and 3435 C > T carriership were associated with higher blood plasma rivaroxaban concentration and bleeding complications. 52 Apart from that, there are studies that report no link between 1236C > T, 2677G > T, 3435 C > T and rivaroxaban pharmacokinetics. 53 The present study has proven that gene polymorphisms, usually associated with clopidogrel-related bleeding, play an important role in combined antithrombotic therapy: CYP2C19*17 carriers twice as often had low residual platelet reactivity (PRU less than 95) 17.2% vs 33.3% (p = 0.059).…”
Section: Discussionmentioning
confidence: 99%
“…20 Likewise, ABCB1 2677G > T and 3435 C > T carriership were associated with higher blood plasma rivaroxaban concentration and bleeding complications. 52 Apart from that, there are studies that report no link between 1236C > T, 2677G > T, 3435 C > T and rivaroxaban pharmacokinetics. 53 The present study has proven that gene polymorphisms, usually associated with clopidogrel-related bleeding, play an important role in combined antithrombotic therapy: CYP2C19*17 carriers twice as often had low residual platelet reactivity (PRU less than 95) 17.2% vs 33.3% (p = 0.059).…”
Section: Discussionmentioning
confidence: 99%
“…The inappropriate use of DOAC has also been highlighted in this respect [ 18 , 19 ]. In addition, ABCB1 genetic polymorphisms have recently been suggested to contribute to high rivaroxaban levels in a patient admitted for gastrointestinal bleeding [ 20 ]. Therefore, a second objective was to investigate and discuss the presence of such risk factors for bleeding events in our rivaroxaban patients.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, since only a third of rivaroxaban is excreted through renal pathway and since the renal impairment was resolved as soon as four days, it is suggested that genotypes on two SNPs of ABCB1 gene might play a role in compromised drug clearance. There are more than 100 SNPs in ABCB1 gene region occurring at frequency higher than 5%, while two markers investigated in this study have inter-racial prevalence range of 2-90%, which points out to the fact that many other ABCB1 variants are still to be studied (Table 1) [33].…”
Section: Rivaroxaban Pharmacogeneticsmentioning
confidence: 72%